On Pump versus Off Pump Coronary Artery Bypass Grafting: A Meta Analysis - Singh, Sandeep; Fotedar, Sanjay; Bansal, Abhishek; Prashant, Praveen (Journal of Neonatal Surgery, 2025)
Background: Coronary artery disease (CAD) remains a leading global cause of mortality and morbidity. While both on-pump and off-pump coronary artery bypass grafting (CABG) are used for surgical revascularization, the optimal approach remains debated. On-pump CABG, involving cardiopulmonary bypass (CPB), offers a motionless surgical field but is associated with systemic complications. Off-pump CABG avoids CPB, potentially reducing inflammation, neurocognitive damage, and renal dysfunction, particularly in high-risk patients. However, concerns about incomplete revascularization and long-term graft patency persist. Objective: This meta-analysis aimed to compare clinical outcomes between on-pump and off-pump CABG using data from randomized controlled trials (RCTs) to provide statistically significant evidence. Methods: A systematic search of PubMed, Cochrane Library, Embase, Scopus, and Google Scholar identified eligible RCTs. Studies reporting risk ratios (RRs) and odds ratios (ORs) for clinical outcomes were included. Statistical analyses were conducted using Stata-16 with a random-effects model. Heterogeneity and publication bias were assessed. Results: Seven RCTs were analyzed. The pooled RR for off-pump versus on-pump CABG was 0.93 (95% CI: 0.78–1.07), and the pooled OR was 0.92 (95% CI: 0.75–1.10), indicating no statistically significant difference. Heterogeneity was low to moderate (I² ≈ 30%). Funnel plot inspection showed minimal publication bias. Conclusion: Off-pump CABG demonstrated a slight, non-significant reduction in adverse outcomes compared to on-pump CABG. Both approaches appear comparable in safety and effectiveness. Surgical expertise and patient selection remain crucial in determining the optimal technique